DISCRIMINATION AND ROMA IDENTITY IN SERBIA - Bašić, Goran; Stjelja, Ivana (Pravni zapisi, 2021)
The paper was based on contemporary legal, sociological and anthropological literature concerning the issues of discrimination and integration of Roma, as well as on the data obtained in two research projects realised in 2020: “Research on Social Relations among Ethnic Communities in Serbia” (Institute of Social Sciences) and “Roma Equality through Increased Legal Access” (Minority Rights Group). Results of the former project were based on data collected by quantitative methods (national internet sample and field research), while those of the latter were gathered by means of qualitative methods, i.e. interviews with 42 female and 17 male respondents realised in eight focus groups. Crossing the empirical data pertaining to discrimination of the Roma citizens living in Serbia, with the legislative system which should supress and gradually eliminate all forms of discrimination, indicates the depth of the social dimension of this problem, but also the vagueness and deficiencies of the very system.
Keywords: Roma; discrimination; antigypsyism; social inclusion